Large-scale fire suppression modeling of corrugated cardboard boxes on wood pallets in rack-storage configurations. (July 2017) - Ren, Ning; de Vries, Jaap; Zhou, Xiangyang; Chaos, Marcos; Meredith, Karl V.; Wang, Yi
Abstract: In this study, the fire growth and suppression models in FireFOAM were validated for rack-storage commodities consisting of two solid fuels, namely corrugated cardboard boxes and hardwood pallets, which are referred to as Class 2 commodity. Validation experiments included two fire-growth and two fire-suppression configurations with different rack-storage array heights (3 and 5 tiers). In the suppression study, standard-response upright ceiling sprinklers (K-factor of 160 lpm/bar 1/2 ) were used. The time-resolved chemical heat release rates obtained from the experiments were used to validate the fire growth model. The observed sprinkler activations and fire-spread patterns were used to validate the suppression model. This study identified that lateral flame spread is primarily enabled by flames impinging on the commodity's bottom surfaces. This study also showed that obstructions, such as wood pallets, can significantly impede convective and radiative heat transfer to the underside of the commodity, reducing the lateral flame spread rate. Fire-suppression modeling revealed that both surface water transport and lateral flame spread rates are important when predicting fire-suppression behavior. Therefore, as the rack-storage array height increases, so does the water transport time, which results in the fire becoming more difficult to control. Likewise, as the lateral spread rate increases, e.g., as occurs in the absence of wood pallets, fire-suppression also becomes more difficult. Highlights: FireFOAM model shows good agreements with tests for both free-burn and fire-suppression cases. The fire growth of a rack storage fire can be divided into different stages with different fire growth rates. The lateral flame spread rate is important in determining the suppression effectiveness. Suppression effectiveness reduces for higher array since both fire size and water transport time increase.